Study of apoptosis-stimulating effect of isonicotinic acid derivatives in models of acute and latent EBV infections - Golovan, A.V.; Zagorodnya, S.D.; Nesterova, N.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The search for inducers of apoptosis, which would affect one or several stages of the apoptotic process, is the modern strategy of the therapy of viral diseases and especially of virus-induced tumor growth. The ability of isonicotinic acid derivatives to stimulate apoptosis in Raji lymphoblastoid cells infected with Epstein-Barr virus (EBV) is studied. It is shown that iodine-containing compound PV-1 inhibited expression of Bcl-2 protein after 48 hours in EBV infected cells, i. e., under condition of lytic infection. Compound PV-2 induced a slight decrease in expression of Bcl-2 protein at early point, but this decrease is caused by the direct action of the compound on the processes of cell apoptosis, rather than by viral infection. A mixture of compounds PV-1 and PV-2 (compound PV-10) caused a prolonged inhibition of Bcl-2 protein expression in infected cells, suggesting the involvement of mechanisms of apoptosis associated with virus reproduction. Thus, these compounds were effective under an acute lytic infection development and could prevent the switch to latent infection by inducing apoptosis processes.